2008
DOI: 10.1017/s1368980008002437
|View full text |Cite
|
Sign up to set email alerts
|

Association of diet and lifestyle with blood pressure in the Guangxi Hei Yi Zhuang and Han populations

Abstract: Objective: To detect the association of diet and lifestyle with blood pressure in the Guangxi Hei Yi Zhuang and Han populations. Design: A cross-sectional study of hypertension. Setting: Both populations were from seven to nine villages in Napo County, Guangxi Zhuang Autonomous Region, China. Subjects: A total of 1068 subjects of Hei Yi Zhuang and 933 participants of Han Chinese aged 20-89 years were surveyed by a stratified randomised cluster sampling. Results: The levels of systolic blood pressure and pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
0
18
1
Order By: Relevance
“…Recent cross-sectional studies suggested that cigarette smoking and excessive alcohol consumption are both associated with elevated BP and risk of hypertension in the Chinese adult population. 29,30 Even so, when compared with the trends from 1991 to 2007 in women, the acceleration of awareness, treatment, and control rate was slightly greater in men.…”
Section: Discussionmentioning
confidence: 93%
“…Recent cross-sectional studies suggested that cigarette smoking and excessive alcohol consumption are both associated with elevated BP and risk of hypertension in the Chinese adult population. 29,30 Even so, when compared with the trends from 1991 to 2007 in women, the acceleration of awareness, treatment, and control rate was slightly greater in men.…”
Section: Discussionmentioning
confidence: 93%
“…The individuals with TC>5.17 mmol/l and/or TG>1.70 mmol/l were defined as hyperlipidemic [47][49]. Hypertension was diagnosed according to the criteria of 1999 World Health Organization-International Society of Hypertension Guidelines for the management of hypertension [50], [51]. The diagnostic criteria of overweight and obesity were according to the Cooperative Meta-analysis Group of China Obesity Task Force.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension was diagnosed according to the criteria of 1999 The World Health Organization-International Society of Hypertension Guidelines for the management of hypertension [55], [56]. The diagnostic criteria of overweight and obesity were according to the Cooperative Meta-analysis Group of China Obesity Task Force.…”
Section: Methodsmentioning
confidence: 99%